Final Condition of HIV Patients Infected with COVID-19 after Receiving Hospital Treatment: A Systematic Review - Elin Hidayat; Abu Bakar; Nursalam Nursalam; Retno Indarwati; Herminia Maria (Jurnal Respirasi, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) can attack anyone, including those who have human immunodeficiency virus (HIV) due to low immune systems. This study aimed to evaluate the final condition of people living with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) (PLWHA) who received treatment at the hospital. Methods: A literature investigation of the last three years (2020-2022) were inquired. Electronic databases (Science Direct, Scopus, ProQuest) with case series or case report designs were examined. The titles, abstracts, and full texts were screened to obtain relevant studies. Data tabulation and narrative analysis were conducted, resulting in 14 studies that met the inclusion criteria. Most of them were case series and case report methods. Each study had different numbers of patients and criteria discussing COVID-19 infection in HIV patients. Results: A total of 14 reviewed studies revealed that HIV patients with COVID-19 could recover from the infection if proper treatments were performed. Some articles also stated that self-isolation at home can manage HIV-infected patients who are not yet severe. In the case of patients with severe infections, intensive care is performed using supplemental oxygen or a ventilator to prevent respiratory failure or acute respiratory distress. Conclusion: COVID-19 can worsen the condition of patients with HIV if not appropriately treated. Otherwise, if the proper treatment is properly performed, it can cure the infection.